2010
DOI: 10.4103/0970-0218.62570
|View full text |Cite
|
Sign up to set email alerts
|

Newborn care practices in urban slums of Lucknow city, UP

Abstract: Objectives:To study the knowledge and practices related to newborn care in urban slums of Lucknow city, UP, and to identify critical behaviors, practices, and barriers that influence the survival of newborns.Materials and Methods:A cross-sectional study in urban slums of Lucknow city, UP, included 524 women who had a live birth during last 1 year preceding data collection. Data were analyzed using statistical software SPSS 10.0 for windows.Results:Study findings showed that about half of the deliveries took pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
37
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 3 publications
8
37
2
Order By: Relevance
“…Similar studies from Uganda, (12,13) Nepal, (14) India (15,16) and Pakistan (8,9,17) also reported that majority of home deliveries were conducted by TBAs or a relative / neighbour. For unplanned home deliveries the most common reasons reported were lack of transport, distance to the health facility and lack of escort.…”
Section: "We Deliver Our Babies At Home There Is No Need To Go To a mentioning
confidence: 53%
See 1 more Smart Citation
“…Similar studies from Uganda, (12,13) Nepal, (14) India (15,16) and Pakistan (8,9,17) also reported that majority of home deliveries were conducted by TBAs or a relative / neighbour. For unplanned home deliveries the most common reasons reported were lack of transport, distance to the health facility and lack of escort.…”
Section: "We Deliver Our Babies At Home There Is No Need To Go To a mentioning
confidence: 53%
“…(14,18,19) Similar practices have also been reported in studies from India and Pakistan. (8,9,16,17) In home deliveries, it is considered to be the duty of the TBA to bathe the baby before leaving.…”
Section: "We Deliver Our Babies At Home There Is No Need To Go To a mentioning
confidence: 99%
“…These findings are better than study conducted by Gupta P et al, in which only 15.1% said that baby should not be bathed and only dry up with a clean cloth. 17 Fever was the most commonly known danger sign (41%) and 18% not being aware of any danger sign in new born. Though 49.48% women knew that breast feeding should be initiated in first hour of birth, only 34.02% could correctly tell the period of exclusive breast feeding.…”
mentioning
confidence: 99%
“…18,19 Lower results were observed in a study conducted in Uttar Pradesh. 17 Globally in 2010, approximately 50% of the 19.3 million infants who were not fully vaccinated lived in India, Nigeria and the Democratic Republic of Congo (DRC). 20 Though majority of mothers (97.89%) felt that their babies were completely immunized awareness regarding the name of the vaccines is very poor.…”
mentioning
confidence: 99%
“…It is essential that a baby is born mature, healthy and grows optimally to become a sturdy adult who can participate in the development of the country. 1 New born care is strongly influenced by women's social status, health status, home care practices for mother and new born as well as maternal and new born care services. Traditional care practices at home and in the community inevitably affect maternal and new born health.…”
Section: Introductionmentioning
confidence: 99%